1987
DOI: 10.5636/jgg.39.187
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric disturbances induced by substorm associated electric fields in the low-latitude F-region.

Abstract: Based on the observation of low latitude ionosphere around 600 km altitude by the Hinotori satellite, well-defined signatures of the ionospheric disturbances associated with substorm activities are found. In the wide area of the nightside equatorial region, a remarkable enhancement of local electron density takes place in response to the enhancement of the AE index, with a time delay shorter than the revolution period of the satellite (97 min). The enhanced region is usually accompanied by several signatures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, there are cases when the enhancements are strongly manifested in the crest region and the critical frequency in the equatorial trough is reduced compared to quiet days. Takahashi et al (1987) have reported ionization enhancements at low latitudes during magnetic disturbed conditions. They showed that these enhancements were having an equatorial anomaly like structure having a minimum at the dip equator.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, there are cases when the enhancements are strongly manifested in the crest region and the critical frequency in the equatorial trough is reduced compared to quiet days. Takahashi et al (1987) have reported ionization enhancements at low latitudes during magnetic disturbed conditions. They showed that these enhancements were having an equatorial anomaly like structure having a minimum at the dip equator.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, the absolute magnitudes of negative ΔIRC and positive Δzonal drift driven by HAE‐SAPS are larger than that driven by LAE‐SAPS, indicating a key role of the substorm. Previous studies have reported that a westward electric field at the dayside ionosphere could be established by substorm (e.g., Takahashi et al., 1987; Wei et al., 2009). Thus, during High‐AE periods, an additional westward electric field could be generated.…”
Section: Discussionmentioning
confidence: 97%
“…However, although the fountain effect has weaker strength and does not uplift the F-layer as much as necessary to form the EIA crests, it was able to spread the ionization for a few degrees on either sides of the dip equator as noted in Figure 2b. For more details about the EIA suppression during disturbed and quiet periods, see Abdu et al (1991), Fagundes et al (2016), TakahashiI et al (1987, . Figure 3 shows the day-to-day occurrence of EIA during the year of 2016, where the red bars, green bars, and white bars indicate developed EIA, not developed/absent, and geomagnetically disturbed days, respectively.…”
Section: Eia Day-to-day Variability In Three Different Longitudinal Smentioning
confidence: 99%
“…However, although the fountain effect has weaker strength and does not uplift the F-layer as much as necessary to form the EIA crests, it was able to spread the ionization for a few degrees on either sides of the dip equator as noted in Figure 2b. For more details about the EIA suppression during disturbed and quiet periods, see Abdu et al (1991), Fagundes et al (2016), TakahashiI et al (1987.…”
Section: 1029/2020ja027906mentioning
confidence: 99%